Isolamento e seleção de fungos para o controle do percevejo-marrom - Dalla Nora, Daiane (2019)
The stink bug species Euschistus heros can be controlled by entomopathogenic fungi. However, few researches have been done on the biological control of this species and there is only bio-insecticide available in the market. Therefore, the objective of this work was to isolate and select entomopathogenic fungi and determine the concentration of conidia necessary to control E. heros bug in laboratory conditions. Fungi were isolated from soil samples and from diseased insects. The selection was done by inoculating 5μL of a suspension of 1x108 conidia mL-1 on the back of adult stink bugs and evaluating mortality for 15 days. The three fungi selected were identified by molecular biology techniques and belong to the Beauveria bassiana species. UFSM-1, UFSM-2 and UFSM-26 were selected from 36 isolates for causing 100% mortality in adults of the brown bug, which were tested in bioassays for determination of LC50 and CL90 and accumulated mortality. The fungi UFSM-1 and UFSM-2 got distinguished by the high virulence and rapid lethality in E. heros, because in 9 days, 90% of the stink bugs were killed with the application of 5x109 conidia mL-1 (CL90). For the fungus UFSM-26, the CL90 was 8x1010 conidia mL-1. With the application of 1x108 conidia mL-1, UFSM-1 and UFSM-2 isolates killed 70% of the stink bugs in 9 days, while UFSM-26 killed 12%. The isolates UFSM-1 and UFSM-2 are promising biological control agents of Euschistus heros and therefore will be evaluated in future studies.